CONCOMITANT PYOGENIC LIVER AND INTRAOCULAR ABSCESSES IN KLEBSIELLA ENDOGENOUS ENDOPHTHALMITIS: CASE REPORT AND REVIEW OF LITERATURE. Issue Volume 16:Issues 6(2022) (November 2022) - Fan, Kenneth C.; Patel, Nimesh A.; Sengillo, Jesse D.; Hudson, Julia L.; Davis, Janet L.
Abstract : Supplemental Digital Content is Available in the Text. We present a patient with unilateral Klebsiella pneumoniae endogenous endophthalmitis associated with concurrent intraocular and liver abscesses. The patient underwent pars plana vitrectomy with intravitreal antibiotics and inpatient admission for systemic antibiotics. Ultimately, the patient required enucleation of the eye, reflecting the potentially devastating nature of this disease. Abstract : Purpose: To describe a rare presentation of Klebsiella pneumoniae endogenous endophthalmitis with concurrent intraocular and liver abscesses. Methods: Case Report. Results: A middle-aged man presented with a red and painful eye with a preceding febrile gastrointestinal illness. Examination and work-up revealed concomitant intraocular and liver abscesses that were treated by pars plana vitrectomy, drainage of subretinal abscess, inpatient admission, and systemic antibiotics. The patient ultimately underwent enucleation of the eye because of persistent pain and poor visual prognosis. Conclusion: Klebsiella pneumoniae endogenous endophthalmitis is a rare and potentially devastating disease that requires high clinical suspicion and early diagnosis. Practitioners should consider systemic etiologies and communicate guarded prognoses in this serious systemic disease.